EXPLAINING ANNUITY FORMULAS. - Watson, J. Donald (The Accounting Review, 1936)
The article focuses on interpreting the two principal annuity formulas. It is assumed that the student already understands the formulas for compound interest and compound discount and recognizes them in the said formulas. For calculating annuity, most of the students employ the formula for the sum of a geometric progression. However, the two principal annuity formulas can be explained without reference to a geometric progression and in terms that a student can understand and remember. Without referring to a geometric progression, the author attempts to show why the first formula is compound interest on one divided by the interest rate per period and why the second formula is compound discount on one divided by the interest rate per period. The author believes that the explanations presented in the article are preferable to the usual textbook discussion because the student can see why the annuity formulas are as they are; namely, compound interest on one divided by the interest rate per period and compound discount on one divided by the interest rate per period.